Consulting Report - Municipality of Surco - Thomas, Daneka Danielle (2024)
This report investigates the significant challenges entrepreneurs in Surco, Lima, face particularly the limited access to capital. The analysis emphasizes that the lack of access to formal financing is the main challenge for small and micro-businesses, which make up 90% of businesses in Surco. Additionally, over 70% of these businesses operate informally, which limits their ability to get bank loans or other financial support. Key findings suggest that improving financial literacy, encouraging businesses to formalize, and creating better connections between entrepreneurs and investors are essential steps to building a stronger, more inclusive entrepreneurial ecosystem. The proposed solution focuses on creating a digital platform that connects local entrepreneurs with both local and international investors. This platform offers educational resources and provides certifications to build trust. The platform was built using agile methodologies and it was designed based on user feedback. Its features include a Spanish-language interface, secure communication, and access to business resources, which directly addresses the specific challenges faced by entrepreneurs in the region. This business model not only enhances the local economy but also aligns with global Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation, and Infrastructure). The research concludes that the platform's innovative and disruptive approach can transform Surco's entrepreneurial landscape by offering a sustainable, scalable, and socially responsible solution to the capital access problem.